2001
DOI: 10.1136/jnnp.71.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Alzheimer's disease and dementia with Lewy bodies mistaken for Creutzfeldt-Jakob disease

Abstract: Objectives-To describe the clinical presentation of patients with Alzheimer's disease (AD) or dementia with Lewy bodies (DLB) who were suspected of having Creutzfeldt-Jakob disease (CJD) and to investigate whether current clinical diagnostic criteria cover these atypical forms of AD and DLB. Methods-Brains from necropsy were examined for the diagnosis of CJD at the German reference centre for spongiform encephalopathies. Symptoms and signs in patients with suspected CJD in whom necropsy showed AD (n=19) or DLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 37 publications
(46 reference statements)
8
92
0
15
Order By: Relevance
“…In view of the recent reports suggesting that PrP c is upregulated in certain neuropathological conditions (Esiri et al 2000), including in AD (Ferrer et al 2001;Voigtländer et al 2001), we examined the expression of PrP c in frozen sections from the frontal and occipital lobe in AD and DLBD-two well-characterized neurodegenerative disorders that share certain clinical and pathological characteristics with CJD (DeArmond 1993; Budka et al 1995;Hsiao 1997;Haïk et al 2000;Tschampa et al 2001;Castellani et al 2004), and in normal control cases. This is significant because unlike routine paraffin-embedded materials, the tissues in our study had not been previously subjected to long-term fixation in aldehyde-based fixatives (notably formalin) and antigenicity was therefore well preserved by comparison.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the recent reports suggesting that PrP c is upregulated in certain neuropathological conditions (Esiri et al 2000), including in AD (Ferrer et al 2001;Voigtländer et al 2001), we examined the expression of PrP c in frozen sections from the frontal and occipital lobe in AD and DLBD-two well-characterized neurodegenerative disorders that share certain clinical and pathological characteristics with CJD (DeArmond 1993; Budka et al 1995;Hsiao 1997;Haïk et al 2000;Tschampa et al 2001;Castellani et al 2004), and in normal control cases. This is significant because unlike routine paraffin-embedded materials, the tissues in our study had not been previously subjected to long-term fixation in aldehyde-based fixatives (notably formalin) and antigenicity was therefore well preserved by comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that Alzheimer's disease (AD) is the most frequent alternative diagnosis for CJD [3][4][5][6][7]. Although, generally, there is little difficulty in making a differential diagnosis between CJD and AD, some atypical cases of CJD may present with slowly progressive clinical course mimicking AD [8].…”
Section: Introductionmentioning
confidence: 99%
“…PSWCs, however, might also be seen in hepatic encephalopathy, HE, end-stage AD and DLB, and possibly other conditions. 25,31 Brain biopsy Brain biopsy is sometimes necessary when the less invasive workup is nondiagnostic. At our center, we found that brain biopsy was diagnostic in 65% of patients with RPD (excluding nonlymphomatous tumors or patients with HIV), and the results led to initiation of therapy in 44%.…”
Section: Figurementioning
confidence: 99%